Pengembangan E-LKPD Berbasis Kontekstual Pada Materi Asam Basa - Amalia Fitri, Rizkia; Anwar, Yunita Arian Sani; Junaidi, Eka (Chemistry Education Practice, 2024)
The purpose of the study is to determine: 1) the characteristics of the developed contextually-based E-LKPD on acid-base topic and 2) the level of validity and practicality of contextually-based E-LKPD on acid-base topic. This research is a Research and Development research with a 4D research model (define, design, develop, disseminate). The population in this study were students of class XI IPA SMAN 1 Kediri with a sample of the entire population, namely 42 students because the population were relatively small or less than 100. The results showed that the validity value obtained using the Aiken index (V) was 0.84 in the very category of valid. The level of practicality is measured through student responses to the contextually based E-LKPD. The results of the student response analysis are in the very practical category with a practicality percentage of 91%. Based on these results it can be concluded that the contextually based E-LKPD on acid-base topic developed is feasible and practical for used in learning because it meets the valid and practical categories.